The Effect Of Product Innovation And Competitive Advantage On Sales(Case Study of Syarah Bakery Shop, Bengkulu City) - Merta Kusuma; Ika Siti Nur Dharyanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine "The Influence of Product Innovation and Competitive Advantage on Sales (Case Study of Syarah Bakery Shop, Bengkulu City)". This type of research is quantitative research, research on data measurement and object statistics through calculations. The population in this study were consumers of the Bengkulu City Syarah Bakery Shop. The sampling technique was carried out by nonprobability sampling, so there were 96 respondents in this study. Data collection techniques in this study are observation, interviews, and questionnaires. Research results show that Product Innovation has a positive and significant effect on Sales, Competitive Advantage has a positive and significant effect on Sales, Product Innovation and Competitive Advantage together have a positive and significant effect on Sales.